Analisis framing pemberitaan media: dinamika pengesahan RUU PPRT menggunakan model Robert M. Entman - Novita Kristiyani, Dian (Jurnal Komunikasi Universitas Garut: Hasil Pemikiran dan Penelitian, 2025)
Abstract The year 2024 will be the twentieth year of the blurry portrait of the ratification of the PPRT Bill (Domestic Worker Protection Bill). The increase in the number of cases of violence, reaching 3,308 from 2018 to 2024, is a sign that the ratification of the PPRT Bill is one of the propulsions and gives an impetus to the increase in cases of violence against domestic workers. This research explores how media news is being framed regarding the sharpening of the PPRT Bill. This study uses Robert M. Entman's framing analysis and focuses on problem definition, cause identification, moral assessment, and solution recommendations. A constructivist qualitative approach was chosen to analyze how the four media formed an understanding of the news of the PPRT Bill. This study's observation and analysis units are five news reports from the press: News, VOA Indonesia, Tempo, and Kompas. The result is that framing the four media consistently emphasized the importance of ratifying the PPRT Bill. Politicians, legislatures, and the House of Representatives are seen as having a great responsibility to complete the passage of this bill and protect domestic workers as a vulnerable group. In addition, there is an urgent need for the enforcement of the PPRT Bill to be seen as a crucial step to improve employment conditions and provide legal protection for domestic workers. Encouragement and participation from civil society, the public, and activists are essential factors in driving political change related to this issue. The media also has a crucial role in providing information and pressure for the ratification of the PPRT Bill Keywords: PPRT draft bill, media framing, Robert M. Entman model.   Abstrak Tahun 2024 menjadi tahun ke-duapuluh potret buram pengesahan RUU PPRT (Rancangan Undang-Undang Perlindungan Pekerja Rumah Tangga). Meningkatnya jumlah angka kasus kekerasan mencapai 3.308 dari tahun 2018 hingga tahun 2024 menjadi petanda bahwa pengesahan RUU PPRT menjadi salah satu problematika dan memberi dorongan meningkatnya kasus kekerasan terhadap PRT. Penelitan ini bertujuan untuk mengeskplorasi bagaimana Framing pemberitaan media mengenai pengasahan RUU PPRT. Penelitian ini menggunakan analisis framing Robert M. Entman dan berfokus pada pendefinisian masalah, identifikasi penyebab, penilaian moral, dan rekomendasi penyelesaian. Pendekatan kualitatif konstruktivis dipilih untuk menganalisis bagaimana keempat media membentuk pemahaman mengenai pemberitaan RUU PPRT. Unit amatan dan analisis dalam penelitian ini adalah lima pemberitaan dari media News, VOA Indonesia, Tempo dan Kompas. Hasil yang didapatkan adalah Framing keempat media secara  konsisten menekankan pentingnya pengesahan RUU PPRT. Politisi, legislatif, dan DPR dipandang memiliki tanggung jawab besar untuk menyelesaikan pengesahan RUU ini dan melindungi PRT sebagai kelompok yang rentan. Selain itu ada kebutuhan mendesak bahwa penegsahan RUU PPRT dilihat sebagai langkah krusial untuk memperbaiki kondisi ketenagakerjaan dan memberikan perlindungan hukum bagi PRT. Dorongan dan partisipasi dari masyarakat sipil, publik dan aktivis menjadi faktor penting dalam menggerakkan perubahan politik terkait isu ini. Media juga memiliki peran yang cukup krusial dalam pemberian informasi dan tekanan pengesahan RUU PPRT. Kata-kata kunci: PPRT draft bill, media framing, Robert M. Entman model.